Islamic Pilantrophy as A Mechanism in Improving Agricultural Products and Sustenance in the Refugees Camps of the Lake Chad Basin Sub-Region - Muhammad Auwal Sulaiman (International Journal of Islamic Khazanah, 2023)
The Insecurity crossing the Lake Chad basin and North Eastern Nigeria seriously affected the activities of farming, fishing and other agricultural programs in the region. Lake provide water for irrigation, fishing activities, water for cattle, and link of water transportation across the four counties that shares the lake. The paper fund that many communities abandoned their agricultural activities and relocated to IDPs for their safety of life. This situation caused great lost to the affected communities and many people became unemployed and then falls into poverty every day. Using descriptive and analytical method, this study discusses the socio-economic role of Islamic philanthropy in funding the agricultural sector to restore the sources of livelihoods of the refugees camps of north Eastern Nigeria. philanthropy known as (Waqf) is a voluntary charity in terms of land and property and is proven to be a strong instrument to reduce various burdens of life. Meanwhile, the paper recommends how this will be designed in order to reach the targeted communities.